Using the Web for Canadian History Projects: What Will Children Find? - Bowler, Leanne; Nesset, Valerie; Large, Andrew; Beheshti, Jamshid (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Three perspectives were used to evaluate existing web pages relevant to grade-six students seeking information about Canadian history. They are 1) traditional evaluation criteria, such as the reliability of information based on its currency, its durability and the authority and purpose of its source; 2) usability and design issues and finally; 3) knowledge transfer issues, such as the level of interaction and interpretation. Trois perspectives ont été utilisées pour évaluer la pertinence des pages Web existantes pour des élèves de sixième année primaire recherchant de l’information sur l’Histoire du Canada. Il s’agit : 1) des critères d’évaluation conventionnels tels que la fiabilité de l’information basée sur sa disponibilité et sa durabilité, ainsi que l’autorité et l’objectif de ses sources; 2) des questions d’utilisation et de conception et finalement, 3) des questions de transfert des connaissances, telles que le niveau d’interaction et d’interprétation.